KNIC AS POTENTIAL DESTINACIONS OF RURAL TOURISM - Vujovic, Slavoljub (Economics of Agriculture, 2006)
Target work is to perceive possible phase development Commune Knic, rural development tourism, simultane instructions for action end needs development other prospective rural destinacions et living space Serbia.